Testing the efficiency of rover science protocols for robotic sample selection: A GeoHeuristic Operational Strategies Test. (May 2018) - Yingst, R.A.; Bartley, J.K.; Chidsey, T.C.; Cohen, B.A.; Gilleaudeau, G.J.; Hynek, B.M.; Kah, L.C.; Minitti, M.E.; Williams, R.M.E.; Black, S.; Gemperline, J.; Schaufler, R.; et al.
Abstract: The GHOST field tests are designed to isolate and test science-driven rover operations protocols, to determine best practices. During a recent field test at a potential Mars 2020 landing site analog, we tested two Mars Science Laboratory data-acquisition and decision-making methods to assess resulting science return and sample quality: a linear method, where sites of interest are studied in the order encountered, and a "walkabout-first" method, where sites of interest are examined remotely before down-selecting to a subset of sites that are interrogated with more resource-intensive instruments. The walkabout method cost less time and fewer resources, while increasing confidence in interpretations. Contextual data critical to evaluating site geology was acquired earlier than for the linear method, and given a higher priority, which resulted in development of more mature hypotheses earlier in the analysis process. Combined, this saved time and energy in the collection of data with more limited spatial coverage. Based on these results, we suggest that the walkabout method be used where doing so would provide early context and time for the science team to develop hypotheses-critical tests; and that in gathering context, coverage may be more important than higher resolution. Highlights: We tested the effectiveness of two rover science protocols. We compared the walkabout-first and linear approaches to field work. Walkabout-first saved time and resources. Walkabout-first provides context early, raising confidence in interpretations. Walkabout-first improves the ability to efficiently triage sites of interest.